2012
DOI: 10.1155/2012/312132
|View full text |Cite
|
Sign up to set email alerts
|

Ant Colony Optimisation for Backward Production Scheduling

Abstract: The main objective of a production scheduling system is to assign tasks (orders or jobs) to resources and sequence them as efficiently and economically (optimised) as possible. Achieving this goal is a difficult task in complex environment where capacity is usually limited. In these scenarios, finding an optimal solution—if possible—demands a large amount of computer time. For this reason, in many cases, a good solution that is quickly found is preferred. In such situations, the use of metaheuristics is an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Since the probability of selecting a node also depends on the number of pheromones in the arc, better solutions tend to influence other ants to choose the same path in the future. When all ants complete the required number of trips, the scheduling process ends, and the best responses are presented [26]. Dorigo et al, [27] revealed the ant algorithm steps, which were then adjusted to the parallel machine production scheduling application.…”
Section: Scheduling-based Ant Colony Optimizationmentioning
confidence: 99%
“…Since the probability of selecting a node also depends on the number of pheromones in the arc, better solutions tend to influence other ants to choose the same path in the future. When all ants complete the required number of trips, the scheduling process ends, and the best responses are presented [26]. Dorigo et al, [27] revealed the ant algorithm steps, which were then adjusted to the parallel machine production scheduling application.…”
Section: Scheduling-based Ant Colony Optimizationmentioning
confidence: 99%
“…The scope of solving the applied problems based on the ant algorithm is quite wide. Application of the ant algorithm for planning multiprofile operations in production systems is given in [19,20]. A multi-purpose programming model for optimizing an import crude oil transportation network based on the use of genetic and ant algorithms is given in [21].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In [16], a hybrid algorithm for resource constrained project scheduling problem, named ANGEL have been proposed that combined ACO with GA, while in [17], a hybrid algorithm named ACOSS that combined ACO, local search strategy and a scatter search have been proposed for RCPSP in real time. Many scheduling problems like backward production scheduling [18] were solved by ACO. Another paper [19] had implemented ACO on the project resource scheduling problem.…”
Section: Related Workmentioning
confidence: 99%